(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The ageing population will soon become one of the most demanding Big Societal Challenges that the world will face. In European union the percentage of the population over 60 years old is expected to increase from 20% to 33% between 2015 and 2050. The report reviews and analyses the role and potential of green and social innovations to foster the active ageing through complex research methods such as an in-depth study of main effects and added value of good practices that demonstrate the contribution of green and social innovations. The main objective of the paper is to analyze the main factors related with social and green innovations that foster healthy ageing and effective prevention and security of elderly people at a reasonable cost. The main conclusion of the research is that it demonstrates the potential of social and green innovation to improve the quality of life and personal security of old people while taking into account the new concepts and instruments related with the elements of Active Ageing Index.